Burr formation during dry microdrilling operations. (23rd July 2007) - Jackson, Mark J.; Robinson, Grant M.; Whitfield, Michael D.
Burr formation is a problem in that it interferes with the proper functioning of micro components. A multi-response optimisation method using a Taguchi approach is used for simultaneous minimisation of burr size, namely, burr height and burr thickness when drilling AISI 1018 steel. Taguchi's L25 orthogonal array for each experiment was performed under different conditions of cutting speed, cutting feed, point angle, and lip clearance angle for a 600 µm drill diameter. In the utility concept for multi-response optimisation, the signal-to-noise ratio for each experiment in the orthogonal array was determined by employing weighting factors for burr height and burr thickness. Detailed analysis of ANOVA with the different combinations of weighting factors to determine the contributions of various micro drilling parameters in controlling the burr height and thickness is presented in this paper.